Автоматизована система керування природнім освітленням на приладобудівному виробництві - Усенко, Р. К. (ХНУРЕ, 2020)
The Internet of things is the concept of a computer network of physical objects (“things”) equipped with built-in technologies for interacting with each other or with the external environment, considering the organization of such networks as a phenomenon that can rebuild economic and social processes, eliminating the need for human participation from part of actions and operations.
Keywords: інтернет речей; автоматизована система; природнє освітлення; приладобудівне виробництво